Introducing autonomy in internet of things - Ashraf , Qazi Mamoon; Habaebi, Mohamed Hadi (2015)
Internet of Things (IoT) is playing a major role in extending the reach of the existing communication systems to include resource constrained devices. Many exciting research works for IoT have been proposed for management of such devices such that human intervention is minimized. This is a challenge due to the high heterogeneity, high complexity of the devices and the lack of dynamic management schemes.Here, we introduce the paradigm of autonomic computing to be used for such dynamic yet secure management in IoT. The adoption of the autonomy in IoT architecture can prove to be a valuable addition to IoT systems.